Information System Stock And Chain Supply Smart Platform Web Rule-Based On Store Break Split Ade Wm - Nofita Elfina; Rizaldi Rizaldi; Parini Parini (Brilliance: Research of Artificial Intelligence, 2026)
Inventory management is an important aspect in supporting business operations, especially in the trading sector with a high level of product turnover. At Ade WM Glassware Store, inventory management is still carried out manually, resulting in inaccurate data, delayed information, and difficulties in monitoring stock availability in real-time. In addition, coordination with suppliers is not yet well integrated, which often leads to delays in restocking and imbalanced inventory levels. This study aims to design and develop a web-based intelligent inventory and supply chain information system using a rule-based approach. The research stages include data collection through observation, interviews, and literature study, system requirement analysis, system design using UML, and implementation using PHP and MySQL. The results show that the developed system improves inventory data accuracy, accelerates the recording process, and facilitates real-time monitoring of stock and suppliers. Therefore, the system enhances operational efficiency and supports the optimization of the store’s supply chain.